A double-blind, randomised, placebo-controlled trial of oral midazolam plus oral ketamine for sedation of children during laceration repair. Issue 8 (18th May 2013) - Barkan, Shiri; Breitbart, Rachelle; Brenner-Zada, Galit; Feldon, Michal; Assa, Amit; Toledano, Michal; Berkovitch, Sofia; Shavit, Itai; Kozer, Eran
Abstract : Objectives: To compare the efficacy of oral midazolam alone with a combination of oral midazolam and ketamine in children requiring laceration repair. Design: A randomised, double-blind, placebo-controlled study. Setting: Paediatric emergency department. Participants: Children 1–10 years of age with lacerations requiring sedation. Interventions: Using a computer-generated sequence, children were randomly assigned in blocks of four to one of two groups: oral midazolam (0.5 mg/kg) plus oral placebo and oral midazolam (0.5 mg/kg) plus oral ketamine (5 mg/kg). The allocation sequence was kept by the pharmacy staff, and the investigators were blinded to randomisation until statistical analysis of the study was completed. Main outcome measures: Visual Analogue Scale (VAS) assessment by a parent and Sedation Score assessment by an investigator. Results: 60 children were recruited; 29 were assigned for treatment with midazolam and 31 for the combination of midazolam and ketamine. There were no differences in basic demographics and wound characteristics between the groups. VAS assessment by a parent was 4.5±3.3 mm in the midazolam+ketamine group versus 4.4±2.7 mm in the midazolam alone group (mean difference 0.1, CI −1.9 to 1.71). Sedation Score during procedure was lower in the midazolam+ketamine group (mean difference 1.14, 95% CI 0.67 to 1.6). Intravenous sedation was required in two (6%) of the children in the midazolam+ketamine group, and in eight (27%) in the midazolam alone group. p=0.039. No clinically significant adverse effects were documented in either group. Conclusions: No difference was found in pain assessment during local anaesthetic injection between the group treated with midazolam and ketamine, and the group treated with midazolam alone. The combination of oral midazolam and ketamine led to deeper sedation than midazolam alone, with less children requiring intravenous sedation. Clinical trial registration: The trial was registered in www.clinicaltrials.gov as NCT01470157 .